Cognitive impairment and quality of life among patients with carotid artery stenosis in Pakistan: a cross- sectional study - Muhammad Farman, Khalil Abbass Lashari, Muhammad Arshad, Hamza Khan, Sairis Ali, Talha Yousaf, Saqlain Akhtar (Students’ Supplement of Journal of Rawalpindi Medical College, 2026)
Carotid artery stenosis (CAS) is a significant health problem associated with poor cerebral perfusion, which might negatively affect patients’ psychological, physical, and cognitive health status. This study aimed to examined the relationship between CAS, cognitive status, and quality of life (QoL) among patients with CAS. A cross-sectional study was recruited a convenience sample of 140 adults (≥ 18 years) diagnosed via Doppler ultrasound with CAS of ≥ 10% severity from two tertiary hospitals in P a k i s t a n . Exclusion criteria included patients who had undergone CAS revascularization procedures and those with confirmed psychiatric disorders. Data was collected using three sections; demographic data, the World Health Organization Quality of Life BREF, and the mini-mental state examination tools. About 56.6% of the patients had moderate-severe CAS, and 87.1% had moderate-severe cognitive impairment. A significant association was observed between CAS severity and cognitive impairment (χ2 = 33.91, p < 0.001). Notably, 66% of patients with mild CAS exhibited moderate-to-severe cognitive impairment, rising to 71.3% in those with moderate-to-severe CAS. The overall patents’ QoL was poor while the highest mean was for psychological domain (58.86 ± SD = 16.15), and the lowest mean was for physical domain (45.46 ± SD = 19.62). There was a significant impact of the level of cognitive impairment on physical health [F (138) = 5.31, p < 0.01, η2 = 0.072], psychological health [F (138) = 7.05, p < 0.01, η2 = 0.093], and total QoL score [F (138) = 4.59, p < 0.05, η2 = 0.063]. The hierarchical regression revealed that cognitive status does significantly affect QoL, with severe cognitive impairment being associated with worse QoL. After controlling sociodemographic variables, severe CAS (β = − 0.273, p = 0.015) and severe cognitive impairment (β = − 0.291, p = 0.007) were associated with poor QoL. Patients with CAS exhibited moderate cognitive impairment and reduced QoL, particularly in psychological and social domains. Integrating routine cognitive assessments into clinical evaluations is critical to guide holistic care addressing both vascular and cognitive health. Further interventions are required to reduce the potential for cognitive decline while also enhancing patients’ QoL, particularly by improving emotional well-being, daily functioning, and social engagement. Keywords: Carotid artery stenosis, Cognitive status, Pakistan, Quality of life